Forensic and Legal Aspect of the Contents of Herbal and Supplementary Products - Türkmen, Zeynep; Türkdoğru, Serkan; Mercan, Selda; Açıkkol, Münevver (The Bulletin of Legal Medicine, 2014)
There is an increasing interest in herbal products as alternative or supplementary methods of conventional treatments recently. These products are marketed under the licensed as food supplements by Ministry of Food, Agriculture and Livestock and marketed under the name of herbal therapuetics. Since they are not in the drug product status, licensing procedures and marketing can be varied. The most common problems observed in these products are as the risk of contamination, additives, toxicity and standardization of dose and accuracy of labeling.Direct intoxications related with these products as well as adverse effects due to drug interactions are observed recently. Under these circumstances it was shown that there is a need about serious regulations and practice on manufacturing, licensing, sale and supervision of the herbal products offered to the market under the name of alternative or supplementary products.The purpose of this study was to present our findings obtained from three cases consist of two unlicensed herbal products and one licensed sport supplement, which were admitted to our laboratory for content analysis and to evaluate the provisions of the Turkish Criminal Code according to related cases.Keywords: Herbal products, Sibutramine, Dietary Supplements in Sport, Cinnarizine, GC-MS
Keywords: herbal products; sibutramine; dietary supplements in sport; cinnarizine; gc-ms